Level of gymnastic skill as an intrinsic constraint on postural coordination - Marin, L.; Bardy, B. G.; Bootsma, R. J. (Journal of Sports Sciences, 1999)
In this study, we considered the interacting effects of expertise in gymnastics, the type of support surface and the required frequency of head movement on the emergence of postural modes of coordination. A group of elite female gymnasts and a control group of non-gymnasts were asked to track the fore-aft motion of a target with their heads. Two support surface conditions (a balance beam vs the floor) were crossed with four frequencies of target motion. The relative phase between the angular motion of the ankles and hips was analysed. Two stable patterns emerged: an in-phase mode and an anti-phase mode, with the hip-ankle relative phase close to 0 degrees and 180 degrees, respectively. Increasing target frequency produced a change from in-phase to anti-phase coordination, in conditions where no instructions were given to the participants (Experiment 1) as well as in those where participants were instructed to maintain an in-phase mode for as long as possible (Experiment 2). This change, however, occurred earlier for the non-gymnasts than for the gymnasts. We conclude that 0 degrees and 180 degrees are two stable postural coordination modes, that expertise in gymnastics leads to a functional modification of existing patterns of coordination,and that expertise in general can be considered an intrinsic constraint on coordination.